Factor Analysis of The Change in Attitude of Huria Kristen Batak Protestan (HKBP) Towards Pt Toba Pulp Lestari (TPL) in Environmental Sustainability - Frans Jaswin Manalu, Musdodi (Jurnal Sosiologi Agama, 2024)
This research examines the complex relationship regarding environmental sustainability between Huria Kristen Batak Protestan (HKBP) and PT Toba Pulp Lestari (TPL). The history of deforestation and community displacement by TPL leads to the engagement of HKBP in social movements, resulting in environmental advocacy. Despite TPL’s promise to shift to sustainable practices, TPL resumes deforestation and triggers renewed resistance. Previous studies focus on the impacts of TPL, leaving a gap in understanding the role of HKBP. Through thematic analysis and data triangulation, this research uncovers the environmental irresponsibility of TPL, driven by HKBP’s internal and external gains and challenges in promoting sustainability. The insights obtained explain how religious institutions address ecological issues amidst governance dynamics and highlight the need for such understanding in conservation efforts.